Digital Spatial Models in Technology as a Development Tool of the Intellectual Creative Aspect within Education - R. Anamova, Rushana; Leonova, Svetlana A; G. Nartova, Lidiya; P. Tereshchenko, Viсtor (TEM Journal, 2020)
This is a conceptual approach to knowledge acquisition at technical universities. The emphasis is on the consistent possession of knowledge: the acquisition of new and preservation of the existing ones. At the same time, the grapho-geometric component in technical education is one of the most important elements of fundamental (general engineering) education. It is carried out at the initial stage in the process of studying technical disciplines included in the relevant curricula. Applied geometry plays an important role in this process, and it includes such directions as descriptive geometry, analytic geometry, engineering graphics, and computer graphics that provide spatial interpretation of geometric objects and display them on a plane. This combination of subjects studied significantly enriches the geometric development within student's intellectual world.